Effects of Plant Growth Regulators on Fruit Set and Yield of Taiwan Morus macroura. Issue 1 (December 2020) - Ren, Jiequn; Zhang, Minghai; Chen, Li; Li, Zhinian; Zheng, Zhangyun
Abstract: In recent years, it is a common phenomenon that Taiwan Morus macroura has low fruit set in different mulberry planting areas that occurred popularly in China. This study aims to study the effects of plant growth regulators on fruit set and quality of Taiwan Morus macroura . Field experiments were carried out to investigate ten plant growth regulators, treated with 3 concentration gradients. The result shows that six plant growth regulators had better fruit preservation effect, the yield of mulberry which treated with plant growth regulators were significantly higher than that of control groups. To reserve fruit in fruit mulberry production, 85% 2, 4-DNa SP with 400000 600000 dilution, 99.9% Boron fertilizer SL with 1500 2500 dilution, Amino acid soluble fertilizer SP with 35000 dilution, 80% DA-6 SL with 50000 dilution, 0.03% NAA SL with 50000 dilution and 8% Chlorophenoxyacetic acid sodium salt SP with 3000 6000 dilution are the best from the standpoint of food safety and economics.